(untitled) (Global Journal of Medical Research, 2023)
The high incidence of arterial thrombosis and venous thromboembolic complications in patients with SARS-CoV-2 coronavirus infection indicates the need for an in-depth study of the pathogenetic moments of procoagulant status and a more rational approach to preventive measures The aim of the work was to study clinical cases of thrombotic complications in children with coronavirus infection to substantiate the principles of practical approach to treatment and prevention This article presents clinical cases of thrombotic complications after COVID-19 in four children 12 months 12 16 and 3 years of age